PENAPISAN FITOKIMIA DAN UJI TABIR SURYA EKSTRAK ETANOL DAUN KAKAO (Theobroma cacao L.) SECARA SPEKTROFOTOMETRI UV-Vis - Yohanes M. Abanit ,; Putra J. P. Tjitda ,; Femy J. Donuata , (Journal of Innovation Research and Knowledge, 2024)
Cocoa leaves (Theobroma cacao L.) have potential as a natural sunscreen because they contain polyphenolic compounds in absorbing or reflecting sunlight that has an effect on human skin. The aim of the study was to determine the content of metabolite compounds and sunscreen activity of ethanol extract of cocoa leaves, which was extracted using maceration method with 95% ethanol solvent. The ethanol extract of cocoa leaves was made in several concentration series, namely 400, 500, 600, 700, 800, and 900 ppm to measure the absorbance using UV-Vis Spectrophotometry, then calculated the SPF value and compared with 'X' sunscreen on the market. Quantitative research method with experimental research design. The tool used is UV-Vis spectrophotometry. The results obtained from the ethanol extract of cocoa leaves have alkaloid, flavonoid, tannin and saponin compounds and sunscreen activity with a concentration of 400 ppm (SPF 12.71 ± 0.60); concentration of 500 ppm (SPF 15.68 ± 0.57); concentration of 600 ppm (SPF 19.02 ± 1.15); concentration of 700 ppm (SPF 22.27 ± 0.89); concentration of 800 ppm (SPF 26.60 ± 0.45); and concentration of 900 ppm (SPF 29.26 ± 1.00). The conclusion of the study is that the higher the concentration of cocoa leaf ethanol extract tested, the higher the SPF value produced so that it affects the category of protection against UV radiation exposure